2014
DOI: 10.4028/www.scientific.net/msf.794-796.181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructural Constituents and Applied Thermomechanical Processes on Corrosion Behaviour of Aluminum Alloys Produced with Twin Roll Casting (TRC) Technique

Abstract: Aluminum alloys produced with Twin Roll Casting (TRC) technology still necessitate to be thoroughly investigated in some areas. Corrosion mechanisms operating under special conditions with the contribution of unique features of the microstructure are among those. Materials produced with TRC have unique features inherently generated due to the solidification path of the material during casting. Contrary to the very fine particles at the locations close to the free surface, centerline segregation (CLS) occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[6,11] On the other hand, little work has been done on TRC AA3003. Işıksaçan C. et al [12] studied the effect of the CLS on the corrosion behaviour of two types of alloys, namely an AA3003 and an AA8006 alloy, both used in the construction of heat exchangers. Furthermore, the effect of chemical composition (the Zn content in the AA3003 and the Cu content in the AA8006 alloy) and thermomechanical processing (different homogenization heat treatments) on the corrosion behaviour of the CLS in an HCl-NaCl solution was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,11] On the other hand, little work has been done on TRC AA3003. Işıksaçan C. et al [12] studied the effect of the CLS on the corrosion behaviour of two types of alloys, namely an AA3003 and an AA8006 alloy, both used in the construction of heat exchangers. Furthermore, the effect of chemical composition (the Zn content in the AA3003 and the Cu content in the AA8006 alloy) and thermomechanical processing (different homogenization heat treatments) on the corrosion behaviour of the CLS in an HCl-NaCl solution was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the high Zn-containing AA3003, and the Cu-containing AA8006 alloy with a high homogenization temperature had an increased corrosion activity at the CLS. [12] However, to the best of our knowledge, the effect of a simulated brazing step on the electrochemical properties of AA3003 fin material produced by TRC has not been investigated yet. Furthermore, the cross-section of this AA3003 fin material is exposed at some locations in heat exchangers, so studying both the outer surface as well as its cross-section is of pivotal importance to gain root cause information on microstructural effects on corrosion performance for the material in its final application.…”
Section: Introductionmentioning
confidence: 99%